Relationship between the development of lymphatic and glandular tissue in the larynx - Holibková, A; Výborná, E; Hubácek, J (Acta Universitatis Palackianae Olomucensis Facultatis Medicae, 1989)
A total of 144 human larynxes, both from the prenatal period and from subjects aged from birth to 95 years, were used for the study of the relationship between the development of glandular tissue and the localization of future laryngeal tonsils. The results of our study are represented graphically. It has been found out that at the sites of future tonsils glands make earlier appearance than at the sites of other glandular groups in the larynx. This interrelationship of lymphatic and glandular tissue has not only morphological but also clinical and immunological importance.
Keywords: larynx; stárnutí; Aging; Lymphatic System; lidé; Larynx; Humans; lymfatický systém